Penggunaan Video Company Profile sebagai Sarana Informasi dan Meningkatkan Promosi pada PT Avoir Industry - Aisyah Jasmine; Redito Benaya Loen (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Company Profile is a supporting tool for Public Relations that contains general informations regarding a business entity. It can be categorized into four different types which are website, print, interactive application and video. The Creators chose video as their project base to make a company profile for PT Avoir Industry. It can be used to introduce the company’s identity in order to build quality partnership with external parties and can also be functioned as a promotion channel. PT Avoir Industry has stood since 2008 and in the past 11 years PT Avoir Industry has not yet had the company profile video. The creator feels that a new method is needed for the company to keep up with the development of digital age. In the production of this company profile video, the creators uses three stages, those are:Pre Production, Production and post production. The concept is one that uses a cast ensemble to display the utilization of drinking cup in daily life, which will then lead to production, packaging and distribution process. This video is three to six minutes long. The purpose of the work is to provide information on PT Avoir Industry and to promote the promotion of the company to be better known to the public, especially the market’s targets in the form of a company profile video. The work will be uploaded on four social media platforms those are Instagram, youtube, facebook and the company’s official website. The four platforms have the high potentioal to provide information to the public, especially the target of the market of avoir industries.